(3fShjI ddLejY(B: s (3GdSjGSGJ GdYGWajI(B/ s - (3ghcS, Hjds ((3chjJ;s (3efThQGJ LOd fTQ hJhRjY; s, 2022)
Bell Hooks directs her focus to those unfamiliar with feminism beyond conventional narratives, especially those shaped by patriarchal discourse. She explores the stages of feminist struggle and the transformative contributions that emerged during the feminist revolution of the sixties, seventies, and beyond.
(3aj cJGHgG zGdfShjI ddLejY(B: (3GdSjGSGJ GdYGWajIy JJhLg GdfGbOI hGdeacQI GdfShjI Hjd ghcS HGdOQLI GdChdi Edi nef de jJYqQa Edi GdfShjI EdG NdGd GdCacGQ hGdcJGHGJ GdeSJgdcI MhdgG, Cj cd ef YQa GdfShjI ef NdGd NWGHGJ GdfXGe GdCHhj(B. (3aJJfGhd eQGMd GdfVGd GdfShj hGdESgGeGJ hGdJZjQGJ GdJj fJLJ HaVd GdKhQI GdfShjI aj GdSJjfGJ hGdSHYjfGJ heG HYOgG(B.s
Title translation: Feminism for all- Politics of emotion- Author: Bell Hooks. Translation: Munir Alimi
Arabic
Keywords: 20th century; HQ1-2044 The Family. Marriage. Women- Feminism/Ecofeminism